2007
DOI: 10.1016/j.carbon.2006.09.028
|View full text |Cite
|
Sign up to set email alerts
|

The structural evolution of thin multi-walled carbon nanotubes during isothermal annealing

Abstract: Systematic isothermal annealing has been carried out on catalytic chemical vapor deposition-derived highly disordered multi-walled carbon nanotubes in order to understand the structural evolution of carbon nanotubes kinetically. After specified isothermal time the crystallographic parameters strongly depend on annealing temperature, and can be divided into three stages. Rapid structural enhancement in the range from 1800 to 2200°C originates from the abrupt evolution of the residual catalytic compounds and is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 21 publications
6
38
0
1
Order By: Relevance
“…3 (b) and Table 1). 21,22 In addition, distinctive changes in the R value (I D /I G , the intensity of the D band over the intensity of the G band) from 0.848 to 0.552 were observed for the pristine and heat treated sample at 1500 o C; an observation that is consistent with TEM observations discussed above. Furthermore, the high intensity and symmetry of the G' band (overtone of the D band) at 2700 cm -1 for the sample treated at 2800 o C, also indicates the lack of 3D stacking order, 23 which caused by the mismatching of the concentric cylinders into an ABAB… stacking configuration.…”
Section: Resultssupporting
confidence: 86%
“…3 (b) and Table 1). 21,22 In addition, distinctive changes in the R value (I D /I G , the intensity of the D band over the intensity of the G band) from 0.848 to 0.552 were observed for the pristine and heat treated sample at 1500 o C; an observation that is consistent with TEM observations discussed above. Furthermore, the high intensity and symmetry of the G' band (overtone of the D band) at 2700 cm -1 for the sample treated at 2800 o C, also indicates the lack of 3D stacking order, 23 which caused by the mismatching of the concentric cylinders into an ABAB… stacking configuration.…”
Section: Resultssupporting
confidence: 86%
“…Thermal treatment was carried out in a graphite-resistance furnace operating in a high-purity argon gas atmosphere in a semi-continuous system. The detailed synthesis and thermal treatment conditions have been described in detail in our former paper [23].…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study [23] it has been revealed that the removal of iron catalysts entrapped in carbon nanotubes involved the decomposition of iron compound with sulfur around 1500 °C and the vaporization of different Fe phases during isothermal treatment. However, until now there is no detailed information about the composition and the remained amount of every Fe phases for thermal treated CCVD-derived MWCNTs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complexation with appropriate ligands seems a good solution, as the complexed metal ion have an increased solubility in supercritical CO 2 . The complexing agents must have high stability constants at low pH, high solubility in the SF and fast kinetics of complexation 7 . The extraction of metal ions in the aqueous phase by chelating agents can occur by the formation of extractable complexes such as β-diketonates and organophosphates.…”
Section: Introductionmentioning
confidence: 99%